Advances in Acoustics and Vibration II Proceedings of the Second International Conference on Acoustics and Vibration (ICAV2018), March 19-21, 2018, Hammamet, Tunisia - Fakhfakh, Tahar; Karra, Chafik; Bouaziz, Slim.; Chaari, Fakher; Haddar, Mohamed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book provides readers with a snapshot of recent research and industrial trends in field of industrial acoustics and vibration. Each chapter, accepted after a rigorous peer-review process, reports on a selected, original piece of work presented and discussed at the Second International Conference on Acoustics and Vibration (ICAV2018), which was organized by the Tunisian Association of Industrial Acoustics and Vibration (ATAVI) and held March 19-21, in Hammamet, Tunisia. The contributions cover advances in both theory and practice in a variety of subfields, such as: smart materials and structures; fluid-structure interaction; structural acoustics as well as computational vibro-acoustics and numerical methods. Further topics include: engines control, noise identification, robust design, flow-induced vibration and many others. This book provides a valuable resource for both academics and professionals dealing with diverse issues in applied mechanics. By combining advanced theories withindustrial issues, it is expected to facilitate communication and collaboration between different groups of researchers and technology users.
Part 1: Dynamics and fault detection of machinery -- L-kurtosis and Improved Complete Ensemble EMD in early fault detection under variable load band speed -- Dynamic behavior of back to back planetary gear in presence of pitting defects -- Losses in Thrust Ball Bearings Lubricated with Axle Gear Oils -- Dynamic Behavior and Stability of a Flexible Rotor -- Operational Modal Analysis for a half vehicle model -- Detecting sound hard cracks in isotropic inhomogeneities -- On the research of extra characteristic frequencies of a planetary gearbox -- Part 2: Mutiphysics systems dynamics -- Analytical based approach for vibration analysis in Modelica: application to the bridge crane system.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Acoustical engineering; Engineering design; Security systems; Multibody Systems and Mechanical Vibrations; Engineering Acoustics; Engineering Design; Security Science and Technology